2007
DOI: 10.1038/sj.ijo.0803766
|View full text |Cite
|
Sign up to set email alerts
|

A new variation in the promoter region, the −604 C>T, and the Leu72Met polymorphism of the ghrelin gene are associated with protection to insulin resistance

Abstract: Objective: Previous studies suggested that polymorphisms in the coding region of the preproghrelin were involved in the etiology of obesity and might modulate glucose-induced insulin secretion. We evaluated the association of a new variation, À604C4T, in the promoter region of the ghrelin gene, of Leu72Met (247C4A) and of Gln90Leu (265A4T), all haplotypetagging single nucleotide polymorphisms (SNPs), with measures of insulin sensitivity in 1420 adult individuals. Research methods: The three SNPs were genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
(45 reference statements)
4
23
0
1
Order By: Relevance
“…This finding is concordant with the association between ghrelin promoter polymorphism rs26311 and homeostasis model assessment‐insulin resistance that was reported in a Korean cohort (68). Another group also suggested that ghrelin rs27647 and rs696217 variants can modulate insulin sensitivity (69). We could further speculate that ghrelin and GHSR genes may modulate the programming of glucose‐insulin metabolism and of growth hormone/insulin‐like growth factor 1/insulin axis, the latter regulating the former together with the nutritional environment (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is concordant with the association between ghrelin promoter polymorphism rs26311 and homeostasis model assessment‐insulin resistance that was reported in a Korean cohort (68). Another group also suggested that ghrelin rs27647 and rs696217 variants can modulate insulin sensitivity (69). We could further speculate that ghrelin and GHSR genes may modulate the programming of glucose‐insulin metabolism and of growth hormone/insulin‐like growth factor 1/insulin axis, the latter regulating the former together with the nutritional environment (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…Zavarella et al evaluated the association of a new variation, À604C4T, in the promoter region of the ghrelin gene, of Leu72Met (247C4A) and of Gln90Leu (265A4T), all haplotype-tagging SNPs, with measures of insulin sensitivity in 1420 adult individuals. They suggested a protective role of the Met72 variant and of À604 T allele in modulating insulin resistance [4]. Kim et al observed that the preproghrelin Leu72Met polymorphisms is not associated with DM type 2.…”
Section: Discussionmentioning
confidence: 98%
“…We wanted to assess the role of these two polymorphisms in AITDs, as in the current literature they were more frequently responsible for endocrinopathies, such as type 2 diabetes, obesity, insulin resistance, metabolic syndrome, anorexia nervosa. The other polymorphism, such as rs34911341 C4T, is rare [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The single nucleotide polymorphisms (SNPs) considered in this study were leptin ( LEP ) (rs7799039), leptin receptor ( LEPR ) (rs1137101), ghrelin/obestatin prepropeptide ( GHRL ) (rs696217), neuropeptide Y ( NPY ) (rs16139), adrenoceptor beta 2, surface ( ADRB2 ) (rs1042713), adrenoceptor beta-3 ( ADRB3 ) (rs4994), and uncoupling protein 3 (mitochondrial, proton carrier) ( UCP3 ) (rs1800849). These SNPs were selected because 1) their genes regulate energy intake ( LEP, LEPR, GHRL, and NPY) or energy expenditure ( ADRB2, ADRB3, and UCP3) , 14,15,22 2) they have established or potential functional impact; 14,2330 the five of the seven selected SNPs are missense mutations (rs7799039 and rs1800849 are not missense), and 3) they are common (minor allele frequency >5%) among European Americans (the NCBI SNP database: http://www.ncbi.nlm.nih.gov). SNP genotyping was conducted with TaqMan SNP Genotyping Assays (Life Technology, Grand Island, NY) in a laboratory (Fred Kadlubar, PhD) of the Division of Medical Genetics, University of Arkansas for Medical Sciences.…”
Section: Methodsmentioning
confidence: 99%